Taḥsīn wa taqbīḥ-i Thaʿālibī - al-Thaʿālibī, Abū Manṣūr (Miras Maktoob, ISBN: 9789004365452., 2019)
Abū Manṣūr al-Thaʿālibī (d. 429/1038) was a very productive writer in Arabic philology and belles lettres and a promotor of the Arabic language in the eastern lands of the Islamic word. Born in Nishapur, it was there that he began his career, forging bonds of friendship with influential literati and various men of state. From there he travelled to the courts of different rulers in some of the major cities in Transoxania and Khurāsān, finally to return to Nishapur where he spent the last years of his life. A compiler and literary critic more than an author in his own right, al-Thaʿālibī's literary anthologies have done much for the preservation of early Arabic literature-mostly poetry-otherwise lost. As explained by the editor, the present work is not a Persian rendering of his Taḥsīn al-qabīḥ wa-taqbīḥ al-ḥasan , but probably done from an Arabic original that was similar to two of Thaʿālibī's other compilatory works.